OP0225 Three Months' Clinical Outcomes from A Nationwide Non-Medical Switch from Originator To Biosimilar Infliximab in Patients with Inflammatory Arthritis. Results from The Danbio Registry. (15th July 2016) - Glintborg, B.; Juul Sørensen, I.; Vendelbo Jensen, D.; Krogh, N.S.; Loft, A.G.; Colic, A.; Espesen, J.; Olsen, J.; Hendricks, O.; Grydehøj, J.; Hansen, I.M.J.; Sørensen, M.V.; et al.
Abstract : Background: According to national guidelines issued in 2015, a non-medical switch from originator infliximab (IFX) (Remicade) to biosimilar Remsima was conducted in all Danish patients with inflammatory rheumatic diseases treated in routine care. Objectives: To investigate 3 months' clinical outcomes in Remicade-treated patients (pts) with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondyloarthrits (SpA) who switched to Remsima and were monitored prospectively in the DANBIO registry. Methods: Disease activity at 3 mths before switch (pre-switch), at the switch and after 3 mths (70–120 days) (post-switch) and changes over time (Δpre-switch and Δpost-switch) were calculated. Disease flare was defined as ΔDAS28≥1.2 (RA/PsA) or ΔASDAS≥1.3 (SpA). Reasons for withdrawal (adverse events (AE), lack of effect (LOE) or other) were registered. Results: 647 of 693 switching pts (300 RA, 96 PsA, 219 SpA, 32 other) had available data (52% women, age (median (IQR) 56 (45–66) yrs)). Prior Remicade treatment duration was 6.7 (4.1–9.4) yrs and in 77% it was the first biological treatment. Remsima dose was in RA+PSA 3.3 (3.0–4.8) mg/kg every 7 (6–8) wks and in SpA 4.8 (3.6–5.1) mg/kg every 6 (6–9) wks. Concomitant MTX was given in 69% (RA+PsA)/25% (SpA). Median follow-up time was 139 (98–160) days. Disease activity remained largely unchanged 3 months prior to vs. after the switch (Table). The proportion of patients with disease flare pre-/post switch was 10%/10% (RA+PsA) (p=1.0) and 10%/0% (SpA) (p=1.0) (related samples McNemar test). Overall, 45 ptts (7%) stopped Remsima treatment during follow-up (AE 16 (allergic 3, infection 2, rash 2, unspecific 9), LOE 20, remission 3, cancer 2, other 4). Prior Remicade treatment duration in these patients was 5.9 (3.5–9.1) yrs. Conclusions: In 647 patients with inflammatory rheumatic diseases treated with Remicade for >4 years, disease activity was largely unaffected in the majority of patients 3 months after non-medical switch to biosimilar Remsima and comparable to the fluctuations observed in the 3 months prior to the switch. However, several patients (∼6%) stopped treatment due to LOE or AE. This warrants further investigation before such a non-medical switch can be recommended. Disclosure of Interest: None declared